Severe Blood–Brain Barrier Disruption in Cardioembolic Stroke - Liu, Chang; Shi, Feina; Chen, Zhicai; Yan, Shenqiang; Ding, Xinfa; Lou, Min (Frontiers in Neurology, 2018)
Background: Previous studies demonstrated that cardioembolism (CE) was prone to develop hemorrhagic transformation (HT), whereas hyper-permeability of blood-brain barrier (BBB) might be one reason for the development of HT. We thus aimed to investigate whether the BBB permeability (BBBP) was higher in CE stroke than other stroke subtypes in acute ischemic stroke patients. Methods: This study was a retrospective review of prospectively collected clinical and imaging database of acute ischemic stroke patients who underwent CT perfusion (CTP). Hypoperfusion was defined as Tmax > 6 seconds. The average relative permeability-surface area product (rPS), reflecting the BBBP, was calculated within the hypoperfusion region (rPShypo). CE was diagnosed according to the international Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. Receiver operating characteristics (ROC) curve analysis was used to determine predictive value of rPShypo for CE. Logistic regression was used to identify independent predictors for CE. Results: A total of 187 patients were included in the final analysis (median age, 73 (61-80) years; 75 (40.1%) females; median baseline NIHSS score, 12 (7-16)). Median rPShypo was 65.5 (35.8-110.1) %. Ninety-seven (51.9%) patients were diagnosed as CE. ROC analysis revealed that the optimal rPShypo threshold for CE was 86.71%. The value of rPShypo and the rate of rPShypo > 86.71% were significantly higher in patients with CE than other stroke subtypes (p < 0.05), after adjusting for the potential confounds. Conclusion: The extent of BBB disruption is more severe in CE stroke than other stroke subtypes during the hyperacute stage.